Implementation of Science, Technology, Engineering, and Mathematics (STEM) Models to Improve Student’s Critical Thinking Abilities in Science Learning in Primary Schools - Kamilah, Zahidah Nurul; Nuraeni, Fitri; Alindra, Afridha Laily (Educational Studies and Research Journal, 2024)
Critical thinking ability is one of the abilities that every student in Indonesia needs to have, especially when learning science. Based on the researcher's initial data, the results of daily tests in science subjects obtained an average of ≥ 75 of 64 with a percentage of completion of classical results of 22.22%. Apart from that, there is data from interviews with teachers, that class VD has not implemented innovative learning models in science learning in class VD. It can be concluded that class 5D at SDN 1 Tegalmunjul still requires actions that can innovate classroom learning and improve students' critical thinking abilities in science learning, therefore the STEM learning model is applied to determine the process of student learning activities and increase students' critical thinking abilities in science learning after implementing the STEM learning model. This research uses classroom action research (PTK) with a Kemmis and Taggart research design. The subjects of this research were 27 class VD students at an elementary school in Purwakarta Regency. This research instrument uses critical thinking ability tests in the form of written description tests, and student and teacher activity observation sheets. The percentage of students' critical thinking ability test results in one class in cycle 1 was 33.3%, rising to 88.8% in cycle 2. So, applying the STEM learning model can improve students' critical thinking abilities in science learning in elementary schools.